Quadricuspid Aortic Valve: An Overview (Cardiovascular Journal, 2024)
Quadricuspid aortic valve (QAV) is a rare congenital heart disease. The functional status of QAV is predominantly a pure aortic regurgitation. Clinical manifestations of patients with a QAV depend on the functional status of the QAV and the associated disorders. Significant valvular regurgitation and (or) stenosis is often present with subsequent operation performed at the fifth to sixth decade of life. The functional status of QAV is predominantly regurgitant; whereas pure stenotic QAV can be as few as in only 0.7% of the patients. QAV is usually an isolated anomaly, but other congenital heart defects can be present in 18- 32% of the patients. About one-fifth of them require a surgical operation. Tricuspidalization is a preferred technique for QAV repair. As not all the patients with a QAV necessarily warrant a surgical operation, decision-making in patient selection and surgical procedure of choice are crucial. Antibiotic prophylaxis against infective endocarditis is necessary in the QAV patients with unequal-sized cusps.Cardiovasc j 2024; 16(2): 114-121